We'd rather pay than change the politics of German non-adjustment in the Eurozone crisis - Nils Redeker; Stefanie Walter (The Review of International Organizations, 2020)
Germany's large current account surplus has been widely criticized, especially against the backdrop of the role of macroeconomic imbalances in the Eurozone crisis. We argue that Germany's resistance to reduce its massive current account surplus through an expansionary policy at home is rooted in distributive struggles about the design of possible adjustment policies. To explore this argument, we leverage original survey data from 135 German economic interest groups, qualitative interviews with interest group representatives and policymakers, and data from public opinion surveys. We show that while there is general support for internal adjustment among German interest groups, they disagree heavily about which specific policies should be implemented to achieve this goal. Together with a broad public and elite-based consensus to avoid a break-up of the Eurozone, this polarization turns financing into a politically attractive strategy. Rather than being rooted only in German ordoliberal ideas or Germany's export-oriented structure, distributive conflicts contribute significantly to Germany's resistance to reduce its large current-account surplus. Because similar dynamics can be observed in other surplus countries, we argue that distributive struggles within surplus countries played an important role in interstate conflicts about the management of the crisis.
Keywords: 320; International political economy; Comparative political economy; Eurozone crisis; Global imbalances; Distributional conflicts; Interest groups; Germany